2021
DOI: 10.1186/s12903-021-01506-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness, and perception of dental students, interns, and freshly graduated dentists regarding dental implant complications in Saudi Arabia: a web-based anonymous survey

Abstract: Background It is necessary for dental students and freshly graduated dentists to apply their education and practice to different clinical and preclinical procedures. The implant success rate and durability are high. Therefore, this study was designed to assess the level of knowledge, awareness and perception of dental students, interns and freshly graduated students regarding dental implant complications in Saudi Arabia. Methods A cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
3
7
1
Order By: Relevance
“…This might be related to the fact that in our country, males and married people primarily work outside to earn money for their families. Male predominance is not parallel to another study on awareness about the replacement of missing tooth/teeth [13,15,16], while it agreed with another study in Saudi Arabia that found more male participants [17]. Educated and rural people are also predominant, which might be because this kind of people agreed to take part in the study, and most of them lled out the questionnaire.…”
Section: Discussioncontrasting
confidence: 56%
“…This might be related to the fact that in our country, males and married people primarily work outside to earn money for their families. Male predominance is not parallel to another study on awareness about the replacement of missing tooth/teeth [13,15,16], while it agreed with another study in Saudi Arabia that found more male participants [17]. Educated and rural people are also predominant, which might be because this kind of people agreed to take part in the study, and most of them lled out the questionnaire.…”
Section: Discussioncontrasting
confidence: 56%
“…This could be related to differences in the individual knowledge and interest of participants, or it could indicate that DI courses need to be modified to include all topics relevant to DI treatment planning and communication with patients. 17 Of the 16 DIC included in our study, the highest proportion of correct responses was related to old age, glycemic control, active chemotherapy, and IV Bisphosphonates. This is good but inadequate, and more emphasis should be placed on DI in dental colleges, and in continuous education programs.…”
Section: Discussionmentioning
confidence: 79%
“…This may indicate that DI training could have received greater attention in the programs of in the Saudi government dental colleges, than the other universities, although the data from our study is insufficient to make such conclusions. A recent study in KSA 17 reported that Saudi GDPs, interns, and students showed moderate knowledge of DI complications, with the variation in knowledge based on the place of graduation. When the responses were compared in terms of the highest qualification attained in DI, it was observed that holders of a master's degree achieved the highest scores, which is logical taking into consideration the availability of well-structured postgraduate programs in DI, within and outside the Kingdom.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many more general dentistry practitioners will certainly wish to give dental implant treatment as dental implant sales continue to climb, as public knowledge and demand increases. 8 Although implant dentistry has developed to become an essential component of dental practice, undergraduate curriculum coverage of dental implant research has been sluggish, unstructured, and certainly restricted. To prepare students to become competent and skilled dental practitioners, undergraduate education must keep up with the speed of innovation while remaining in touch with day-to-day professional practice.…”
mentioning
confidence: 99%